Ipsilateral Rupture of Quadriceps Tendon with Distal Tibia Fracture: A Case Report and Review of the Literature. (21st May 2017) - Banerjee, Samik; Dooley, Timothy P.; Parkinson, James R.
Abstract : Traumatic rupture of the quadriceps tendon by itself is not an uncommon clinical condition. However, its association with concurrent ipsilateral closed distal tibia oblique fracture is exceedingly rare with only one previously reported case in English literature. The dual diagnosis of this atypical combination of injury may be masked by pain and immobilization of the more obvious fracture and may be missed, unless the treating physician maintains a high index of suspicion. Suprapatellar knee pain with or without a palpable gap in the quadriceps tendon and inability to straight leg raise in the setting of a distal tibia fracture should raise concern, but if initial treatment employs a long-leg splint the knee symptoms may be muted. In this report, we describe this unusual combination of injury in a 67-year-old male patient who sustained a trivial twisting injury to the leg. The aim of this report is to raise awareness and emphasize the importance of thorough and repeated clinical examinations in the presence of distracting injuries. Despite the complexity of the problem, standard techniques for quadriceps tendon repair using transpatellar bone tunnels following locked intramedullary rodding of the tibia fracture may lead to optimal outcomes.